Notes on Land Grant, Glynn County, 1887 - State of Georgia, Glynn County (Valdosta, GA: Valdosta State University Archives and Special Collections, 2020, 1887)
Notes on Land Grant, Glynn County, 1887. Handwritten notes on ruled Goodyear and Kay, Attorneys at Law stationery. Regarding grant to JM Tison for 140 acres. Brunswick, Ga., July 10, 1887. 2 pages.
1 electronic document [PDF/A]. Includes TIFF and JP2 images. Digitized by the Digital Library of Georgia, September 2019.
Keywords: Deeds; Glynn County (Ga.); Records and correspondence; Court records